Clinical-Epidemiological Profile of Influenza A H1N1 Cases at a Tertiary Care Institute of India - Vijaydeep Siddharth; Vineet Goyal; Vipin Kumar Koushal (Wolters Kluwer Medknow Publications, 2012)
Introduction: Influenza virus is a common human pathogen that has caused serious respiratory illness and death over the past century. In April 2009, a new strain of Influenza virus A H1N1, commonly referred to as "swine flu," began to spread in several countries around the world, and India confirmed its first case on 16 May 16 2009. Aim: To study the clinical and epidemiological profile of Influenza A H1N1 cases at the Government Medical College and Hospital, Chandigarh. Materials and Methods: Clinical epidemiological characteristics of Influenza A H1N1 cases from May 2009 to April 2010 were retrospectively, descriptively analyzed using data from the Influenza A H1N1 screening center and isolation ward at the Government Medical College and Hospital, Chandigarh. Data were Analyzed using MS Excel software. Results: At GMCH, till April 2010, a total of 4379 patients were screened for Influenza A H1N1, of which 365 patients were tested. The most common symptoms were fever (87.6%), cough (49.77%), sore throat (27%) and breathlessness (23.9%). The most common presentation (42.30%) of Influenza A H1N1 cases was fever and cold-like features, not cough. 29.58% (108) of the tested patients were found to be positive for the disease. Maximum cases were detected in the month of December, and the patients less than 40 years of age accounted for 81.4% (44 cases) of the cases. Influenza A H1N1 resulted in death of 54.9% (28) of the admitted cases, of which 46% (12) deaths occurred within 48 h of admission. Conclusion: On the basis of these findings, it can be safely hypothesized that prevalence of Influenza A H1N1 is high in the younger population, and fever, cough and sore throat are the most common symptoms with which the patients usually present.